Replacement therapy with plasma-derived factor VIII concentrates induces skew in T-cell receptor usage and clonal expansion of CD8+ T-cell in HIV-seronegative hemophilia patients - Matsutani, Takaji; Sakurai, Yoshihiko; Yoshioka, Takeshi; Tsuruta, Yuji; Suzuki, Ryuji; Shima, Midori; Yoshioka, Akira (Thrombosis and Haemostasis, 2003)
Replacement therapy with factor VIII (FVIII) products causes immune abnormalities in human immunodeficiency virus (HIV)-seronegative hemophilia patients. However, the question remains why an absolute increase in the number of CD8+ T-cells and diminished proliferation responses of lymphocytes to antigen stimulation in vitro occurs in HIV-seronegative hemophilia patients.To examine whether the FVIII products induce skewing of T-cell receptor (TCR) repertoires, TCR variable region α-chain and β–chain repertoires were analyzed for peripheral blood mononuclear cells (PBMCs) from 15 hemophilia patients treated with heated and/or non-heated plasma-derived FVIII concentrates and 10 age-matched healthy adults. Also, T-cell clonality was compared between these groups using complementarity-determining region 3 (CDR3) size spectratyping. The skewing of TCR repertoires was significantly greater for hemophilia patients than healthy controls. The extent of T-cell clonality was greater for hemophilia patients than the controls, indicating that clonal T-cells frequently expanded in hemophilia patients. The skew in TCR usage and clonal expansion were primarily observed in patients treated with non-heated plasma-derived products.The spectratyping and sequencing of CDR3 regions revealed that the clonal expansion of T-cells was observed for CD8+ T-cells, but not CD4+ T-cells.These results suggest that extensive expansion of CD8+ T-cells is induced by some viruses other than HIV present in FVIII preparations, and the resulting accumulation of CD8+ T-cells is responsible for changes in peripheral T-cell population in HIV-seronegative hemophilia patients.
Keywords: Hemophilia; T lymphocytes; T cell receptors; clonal expansion